التفكير الإيجابي بين النظريات الغربية والهدي النبوي: دراسة تحليلية - Norhayati binti Mat Nor (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The aim of this thesis is to study the ahadith concerning the concept of positive thinking and good impression (ḥusn alẓan), and to identify the areas of agreement and disagreement between two different worldviews: Western and Islamic worldview. The researcher used the inductive method in studying the ahadith in two specific fields: aqidah and ethics from various ahadith books and literatures. In identifying the psychological theories and classifying the related ahadith about positive thinking, the researcher follows the same inductive method, as well as in explaining the status of ahadith. The study also used comparative method, this consist of comparing the concept of positive thinking between Western and Islamic worldviews. The researcher has also applied the analytical method in analysing ahadith and concluded that positive thinking is a scientific concept that exists in Western or Islamic worldviews, and there is various aspects of agreement and disagreement between them due to the differences of principles and values of life. This study has also summarized that, there is certain conditions when negative thinking or bad impression (su alẓan) become permissible and this has been discussed by Muslim scholars which divided ẓan into four main rules: ḥaram, wajib, mubah, and ja'iz. Finally, the researcher reaches the conclusion that, the method in studying the positive thinking should be expanded in by applying the related theories and ahadith to the different groups of people. This kind of field study is very important in helping those who suffer from psychological problems.